Identification and Characterization of circRNA in Longissimus Dorsi of Different Breeds of Cattle - Liu, Ruili; Liu, Xianxun; Bai, Xuejin; Xiao, Chaozhu; Dong, Yajuan (Frontiers in Genetics, 2020)
Shandong black cattle is a new breed of cattle that is developed by applying modern biotechnology, such as somatic cloning, and conventional breeding methods to Luxi cattle. It is very important to study the function and regulatory mechanism of circRNAs in muscle differentiation among different breeds to improve meat quality and meat production performance and to provide new ideas for beef cattle meat quality improvements and new breed development. Therefore, the goal of this study was to sequence and identify circRNAs in muscle tissues of different breeds of cattle. We used RNA-seq to identify circRNAs in the muscles of two breeds of cattle (Shandong black and Luxi). We identified 14640 circRNAs and found 655 differentially expressed circRNAs. We also analysed the classification and characteristics of circRNAs in muscle tissue. GO and KEGG analyses were used on the parental genes of circRNAs. They were mainly involved in a variety of biological processes, such as muscle fibre development, smooth muscle cell proliferation, bone system morphogenesis, tight junctions and the MAPK, AMPK and mTOR signalling pathways. In addition, we used miRanda to predict the interactions between 14 circRNAs and 11 miRNAs. Based on the above assays, we identified circRNAs (circ0001048、circ0001103、circ0001159、circ0003719、circ0003424、circ0003721、circ0003720、circ0001519、circ0001530、circ0005011、circ0014518、circ0000181、circ0000190、circ0010558).that may play important roles in the regulation of muscle growth and development. Using qRT-PCR, 14 circrnas were randomly selected to verify the real circRNAs. Luciferase reporter gene system was used to verify the binding site of miR-1 in circ0014518. Our results provide more information about circRNAs regulating muscle development in different breeds of cattle and lay a solid foundation for future experiments.